Proses Pengambilan Keputusan Adopsi Inovasi Teknologi Budidaya Kedelai Jenuh Air (Kasus: Labuhan Ratu Enam, Lampung Timur) - Faizaty, Nur Elisa; Rifin, Amzul; Tinaprilla, Netti (AGRARIS: Journal of Agribusiness and Rural Development Research, 2016)
The expansion of crop land to suboptimal land (especially in the outside of Java Island) should be set up as source of agriculture crop production growth. Saturated-soil Cultivation (SSC) Technology is able to improve the productivity of soybean plants up to 4.0 tons/ha in the suboptimal land. This research is aims to examine the decision making process on innovation adoption of soybean Saturated-soil Cultivation (SSC) Technology, conducted in Labuan Ratu Enam Village, East Lampung Regency. Main approaches were used in this research is Rogers’ theory of innovation diffusion. Decision process was divided into four main group of analysis: i) communication channel and general description of stages in the innovation decision, ii) influential variables of respondents’ characteristics on the knowledge stage using Kruskall-Wallis test, iii) influential variables of the innovation’s attributes on the persuasion stage using Spearman Correlation test, and iv) correlation between the stages of innovation decision process using Spearman Correlation test and Mann-Whitney test. The results  shows that i) interpersonal channel is chosen as the way to diffuse SSC innovation to 25 potential farmer adopters through discussion, direct practice, and guidance; ii) the influential variables of individuals’ characteristics are leve of nonformal education and level of motivation, while level of formal education and farming experience is not significant difference in their knowledge level about SSC; iii) there is significant correlation between the level of respondents’ persuasion and their perception on the innovation complexity and triability, but not compatability and observability; iv) each stage of SSC innovation-decision, one stage to another in sequence, has significant positive correlation.